Results of evaluating the functional state of the gastric mucosa in duodenal peptic ulcer by means of a test GastroPanel in workers engaged in the manufacture of nitrogen compounds - Tat'yana Evgen'evna Pomytkina (Терапевтический архив, 2010)
Aim. to study the specific features of working conditions in workers from the chemical plants manufacturing nitrogen compounds by the groups under study and by the time course of changes in the serum levels of gastrin-17 (G-17) and pepsinogen-1 (P-1) in relation to the chemical composition of noxious substances, the length of service, the stage of the disease, and the performed therapy. Subjects and methods. A test GastroPanel was used to study the serum levels of G-17 and P-1 in 54 patients with duodenal peptic ulcer (DPU) who worked at the chemical plants manufacturing nitrogen compounds (a study group) and in 15 healthy individuals (a control group). Results. The objective data on the time course of changes in the functional characteristics (G-17 and P-1) of the gastric mucosa (GM) in patients with DPU vary with the chemical composition of noxious substances and the length of service in chemical industry. The basic therapy for PDU contributes to a positive change in the functional parameters reflecting the state of GM. Conclusion. In patients with DPU, the working conditions at the chemical plants manufacturing nitrogen compounds result in changes in the functional parameters reflecting the state of GM.